The decline of reformed church polity in South Africa - Johannes Smit (In die Skriflig, 2018)
Church polity in South Africa is one of the smaller theological disciplines. Different reasons for this position of the discipline maybe indicated as inter alia bad experiences with church polity with regard to church schisms, the influence of the Zeitgeist, and the lack of development in church polity in comparison to other theological disciplines. This article suggests that the impetus for the decline of reformed church polity should be found within the dominant collegialistic concept of church since the acceptance thereof in South Africa. The effect is a secularised view of the church with regard to its government, the office, the church and the church’s relationship with the state. It is suggested that a new discourse about the church and its polity should be initiated in South Africa to the benefit of the church and its polity, but also to that of the different fields which are involved with ecclesiology in various ways.